The magic finger - Dahl, Roald; Blake, Quentin (London : Viking, 2023)
Angered by a neighboring family's sport hunting, an eight-year-old girl turns her magic finger on them.
3.5
3-6.
Keywords: Hunting -- Fiction; Magic -- Fiction; Hunting -- Fiction; Magic -- Fiction